GATA-3 EXPRESSION IN PERIPHERAL BLOOD LYMPHOCYTES OF PATIENTS WITH BRONCHIAL ASTHMA - V. N. Mineev (SPb RAACI, 2014)
The aim of the study is to establish the features of expression of GATA-3 in peripheral lymphocytes from bronchial asthma patients (BA). Material and methods. 10 healthy controls, 15 patients with allergic (atopic) and 15 persons with non-allergic BA were examined. A transcription factor GATA-3 expressed in peripheral lymphocytes was analyzed by Western blot after the lymphocytes were lysed. Preparation of cell lysates, and Western blotting were performed by means of a standard procedure (Amersham). An antibody against GATA-3 (Abcam, UK) was used. Levels of the protein were analyzed versus β-actin levels using anti-actin antibody (Sigma Aldrich, USA). Results. Expression of GATA-3 was significantly increased in lymphocytes of patients with allergic BA as compared to healthy persons and non-allergic BA patients. The level of GATA-3 negatively correlated with the degree of airflow obstruction and positively correlated with dosage of parenteral steroids administered. Conclusion. GATA-3 may play a key role in the pathophysiology of BA. One may suggest that increased expression of GATA-3 transcription factor in atopic BA underlie high levels of Th2-cytokines production in allergic disease